The educational gradient in intake of energy, macro- and micronutrients in the Tromsø Study 2015-2016 - Nilsen, Linn (UiT Norges arktiske universitet, 2020)
Now published as Nilsen, L., Hopstock, L.A., Skeie, G., Grimsgaard, S. & Lundblad, M.W. (2021). The Educational Gradient in Intake of Energy and Macronutrients in the General Adult and Elderly Population: The Tromsø Study 2015–2016. Nutrients, 13 (2), 405. Available in Munin at https://hdl.handle.net/10037/21835 . Background: Socioeconomic status is associated with inequalities in health. Unhealthy diet is a risk factor for non-communicable diseases, and socioeconomic inequalities exists also in diet. Aim: To investigate the relationship between educational level and the intake of total energy, macro- and micronutrients. Participants: 11,302 individuals (40-96 years) from Tromsø, Norway. Methods: I used data from the Tromsø 7 Study (2015-2016). All inhabitants in Tromsø, aged 40+ years (n=32,591) were invited. A total of 21,083 attended. Diet was assessed using a food-frequency questionnaire (FFQ). Participants who answered <90 % of the FFQ, the 1 % with the highest/lowest energy intake and participants with missing data on education were excluded. To investigate the relationship between education level and diet, linear and logistic regression analysis were used. All analysis were performed in strata of sex and educational level, adjusted for covariates (age, body mass index, physical activity level and smoking status). The intake of macro- and micronutrients was compared with the Nordic Nutrition Recommendations. Results: A positive educational gradient was found for fiber, alcohol, vitamin C, folate and iron, and a negative educational gradient was found for carbohydrates, added sugar and iodine in both sexes. A positive educational gradient was also found for energy, total fat, monounsaturated fatty acids and vitamin D in women, and a negative educational gradient was found for saturated fatty acids in men. Compared to participants with primary education, those with long tertiary education had higher odds of being compliant with seven of eighteen nutrient recommendations presented in this study. ...